Cell Labeling with 15-YNE Is Useful for Tracking Protein Palmitoylation and Metabolic Lipid Flux in the Same Sample - Nadine Merz; Karin Schilling; Dominique Thomas; Lisa Hahnefeld; Sabine Grösch (Molecules)
Protein S-palmitoylation is the process by which a palmitoyl fatty acid is attached to a cysteine residue of a protein via a thioester bond. A range of methodologies are available for the detection of protein S-palmitoylation. In this study, two methods for the S-palmitoylation of different proteins were compared after metabolic labeling of cells with 15-hexadecynoic acid (15-YNE) to ascertain their relative usefulness. It was hypothesized that labeling cells with a traceable lipid would affect lipid metabolism and the cellular lipidome. In this study, we developed a method to track 15-YNE incorporation into lipids using liquid chromatography high-resolution mass spectrometry (LC-HRMS) as well as protein palmitoylation in the same sample. We observed a time- and concentration-dependent S-palmitoylation of calnexin and succinate dehydrogenase complex flavoprotein subunit A (SDHA) depending on the cell type. The detection of S-palmitoylation with a clickable fluorophore or biotin azide followed by immunoprecipitation is shown to be equally useful. 15-YNE was observed to be incorporated into a wide array of lipid classes during the process, yet it did not appear to modify the overall lipid composition of the cells. In conclusion, we show that 15-YNE is a useful tracer to detect both protein S-palmitoylation and lipid metabolism in the same sample.